Exploitation and the Decision to Migrate: The Role of Abuse and Unfavorable Working Conditions in Filipina Domestic Workers' Desire to Return Abroad - George S Naufal; Jr. Malit (Institute of Labor Economics (IZA), 2018)
The Gulf Cooperation Council (GCC) countries host at least 2.4 million foreign domestic workers, who are legally excluded from national labor laws and regulations, thus placing them in precarious social, legal, and economic conditions in the GCC labor markets. Despite the recent growth of academic scholarship on domestic work in the GCC and beyond, little attention has been paid to absconding foreign domestic workers and the complex role abuse plays in determining their future decision to migrate. This paper examines the likelihood that Filipina domestic workers will migrate after absconding from their previous employer. Applying a unique dataset of absconding Filipina domestic workers collected at the Philippine Labor Office (POLO) in Qatar between 2013 - 2015, we find that abuse and poor working conditions do not act as deterrents for future migration. Paradoxically, absconding domestic workers who have been financially abused are more likely to want to return and seek employment abroad. This study offers empirical and theoretical insights into the connection between migrant exploitation and domestic workers' desire to migrate once again.
Keywords: J61; J68; O15; 330; migration; absconding; domestic workers; GCC countries; abuse; mobility